Media Literacy and Involvement of Students of SMK YPC Tasikmalaya in Religious Da'wah Movement in Digital Space - Zakiah, Kiki; Iskandar, Doddy; Supriadi, Yadi; Hantoro, Naditha Rizkya (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2024)
The development of digital technology has transformed how students interact and participate in dakwah activities, particularly through social media. This study aims to analyze how media literacy supports the involvement of SMK YPC Tasikmalaya students in digital religious dakwah movements and how pesantren-based education enhances these capabilities. Using qualitative methods and a case study approach, this research collected data through interviews, observations, and documentation of students' digital dakwah activities. The findings indicate that the media literacy program at SMK YPC Tasikmalaya not only equips students with technical skills to access and disseminate information but also instills religious moderation values to counter radicalism and intolerance in digital dakwah. Media literacy developed through the pesantren approach encourages students to become creators of inclusive, peaceful, and relevant dakwah content tailored to digital audiences. The implications of this research highlight the importance of integrating media literacy into religious education curricula to prepare young generations as productive and moderate digital preachers. With these skills, students can actively disseminate tolerant dakwah messages and foster a harmonious digital community rooted in religious values.